Expression and association data strongly support JARID2 involvement in nonsyndromic cleft lip with or without cleft palate. - Scapoli, Luca; Martinelli, Marcella; Pezzetti, Furio; Palmieri, Annalisa; Girardi, Ambra; Savoia, Anna; Bianco, Anna Monica; Carinci, Francesco (Hum Mutat, 2010)
Nonsyndromic cleft lip with or without cleft palate (CL/P) affects approximately 1 in 1,000 births. Genetic studies have provided evidence for the role of several genes and candidate loci in clefting; however, conflicting results have frequently been obtained and much have to be done to unravel the complex genetics of CL/P. In the present investigation we have focused on the candidate region in 6p23, a region that have been found linked to CL/P in several investigations, in the attempt to find out the susceptibility gene provisionally named OFC1. Gene expression experiments in mice embryo of positional candidate genes revealed that JARID2 was highly and specifically expressed in epithelial cells in merging palatal shelves. A family-based linkage disequilibrium study confirmed the pivotal role of JARID2 in orofacial development and strongly supports a role for this gene in CL/P etiology (multiallelic haplotype test P=6 x 10(-5)). Understanding the molecular role of JARID2 within facial development may offer additional information to further unravel the complex genetics of CL/P.
Keywords: Animals; Cleft Lip; Cleft Palate; DNA Mutational Analysis; Family Health; Female; Gene Expression; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Haplotypes; Humans; In Situ Hybridization; Linkage Disequilibrium; Male; Mice; Mice, Inbred C57BL; Mutation; Nerve Tissue Proteins; Palate; Polycomb Repressive Complex 2; Polymorphism, Single Nucleotide; Pregnancy; Reverse Transcriptase Polymerase Chain Reaction